Poverty impacts of food price increases in Nigeria - Minot, Nicholas; Martin, Will (International Food Policy Research Institute, 2023)
The prices of staple grains on international markets began to rise in mid-2020 in response to higher fertilizer prices and supply constraints associated with the Covid-19 pandemic. They further spiked in early 2022 following the invasion of Ukraine by Russia. This brief examines the impact of these events on poverty in Nigeria. It is part of a series of six such briefs that estimate the poverty impact of higher world prices for staple grains. The other briefs cover Kenya, Ethiopia, Burkina Faso, Niger and Mali (see Minot and Martin, 2023a and 2023b; Martin and Minot, 2023a, 2023b, and 2023c). The methodological approach is similar in all six country studies. First, we examine the effect of the increases in international cereal prices on the real price of key grains in the domestic markets of the country. Second, we estimate the impact of the changes in domestic grain prices on the real income of each household using nationally-representative survey data, taking into account the importance of the commodities in consumption and as a source of income for each household. Finally, we estimate the changes in headcount poverty (the share of people living below the poverty line) based on the changes in real income for each household in the sample. We focus on the prices of maize, wheat, and sorghum for reasons discussed below.